Pemeriksaan Resiko Cedera Pada Anggota UKORDA Unversitas Muhammadiyah Sidoarjo - Bagas Anjasmara; Andi Fadhilah Tenriwulan (STIKes Ibnu Sina Ajibarang, 2024)
Sports injuries are all forms of abnormalities and damages that occur in the body, both in the structure and function of the body that cause pain, resulting from physical movement and sports activities. This activity aims to determine the risk of sports injuries in athletes of UKM Sports Universitas Muhammadiyah Sidoarjo (UKORDA) by using Functional Movement Screening (FMS). UKORDA athletes as participants performed seven movements from the FMS examination consisting of movements consisting of (1) Deep Squat, (2) Hurdle Step, (3) In-Line Lunge, (4) Shoulder Mobility, (5) Active Straight Leg Raise, (6) Truck Stability Push Up, (7) Rotary Stability.The FMS assessment is given based on the effectiveness of the movements carried out by the sample, where the subject will be given a score of